PENERAPAN ALGORITME VIOLA-JONES DAN EIGENFACE PADA SISTEM PENGENALAN WAJAH - , NAFIER RAHMANTHA; , Dr. Indah Soesanti, S.T., M.T ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research in face recognition system becomes very complex and complicated. Face recognition system that has been developed turn out to be difficult since it is sensitive to illumination, expression, orientation, occlusion etc. At least, there are 2 main components in face recognition system such as face detector and face recognition. In this research combines face recognition system which is used Viola-Jones and eigenface algorithm as the main method. By combining both of these algorithms, the automated face recognition system can be made. In this final project was used 7 faces each with 10 different expression. Test results gave a accuracy of system by 95,45%